1994
DOI: 10.1116/1.579081
|View full text |Cite
|
Sign up to set email alerts
|

Si/SiO2 interface studies by spectroscopic immersion ellipsometry and atomic force microscopy

Abstract: The dependence of the Si/SiO2 interface characteristics on the thickness and oxidation temperature for SiO2 films grown on different Si orientations was studied by spectroscopic immersion ellipsometry (SIE) and atomic force microscopy (AFM). Essentially, SIE uses liquids that match the refractive index of the films, thereby optically removing the films and consequently increasing the sensitivity to the interface. We show that as the thickness of the thermally grown SiO2 overlayer increases, the thickness of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(2 citation statements)
references
References 6 publications
1
1
0
Order By: Relevance
“…If an abrupt transition from the a-SiO 2 thin film to c-Si occurs, a one-layer model should work and if there is a transition layer between the main SiO 2 layer and the Si substrate, a two-layer model should be used. Both cases have been reported by other researchers via various characterization techniques [12][13][14][15][16][17][18][19][20]. We checked the one-layer model, two-layer model, surface and interface roughness, layer density and layer thickness.…”
Section: Resultssupporting
confidence: 57%
See 1 more Smart Citation
“…If an abrupt transition from the a-SiO 2 thin film to c-Si occurs, a one-layer model should work and if there is a transition layer between the main SiO 2 layer and the Si substrate, a two-layer model should be used. Both cases have been reported by other researchers via various characterization techniques [12][13][14][15][16][17][18][19][20]. We checked the one-layer model, two-layer model, surface and interface roughness, layer density and layer thickness.…”
Section: Resultssupporting
confidence: 57%
“…Via a high-resolution core-level photoemission spectroscopy measurement, Grunthaner et al [13] and Himpsel et al [14] suggested a substoichiometric interfacial layer of compressed SiO 2 or approximately 1 nm and perhaps extending to 3 nm in thickness. Spectroscopic immersion ellipsometry [15,16], which is an interface sensitive technique, detected a thin layer of higher refractive index, which was interpreted as a region of suboxide formation and compressed SiO 2 . By using x-ray reflectivity, Woronick et al [17] observed the presence of a higher-density interface layer of about 4.5 nm at the SiO 2 /Si interface.…”
Section: Resultsmentioning
confidence: 99%